2022
DOI: 10.3389/fpsyg.2022.874458
|View full text |Cite
|
Sign up to set email alerts
|

Research on the influence of sports participation on school bullying among college students—Chain mediating analysis of emotional intelligence and self-esteem

Abstract: PurposesThis paper aims to discuss the relationship between college students’ sports participation, school bullying, emotional intelligence and self-esteem. At the same time, it explores the intrinsic mechanisms of school bullying, in order to provide a reference for reducing bullying phenomenon among college students, and pave the way for college students to lead happy, healthy and confident lives.MethodsA total of 1,317 students (725 male students, 592 female students, 21.31 ± 3.28 years old) from four unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 79 publications
2
7
0
2
Order By: Relevance
“…The data indicating that boys who are physically active experience less victimisation than boys who are not physically active are consistent with those of the majority of studies [9][10][11][12][13][14][15], although such relationships were not present in the sample as a whole, which is consistent with studies by different authors [16][17][18][19]. In this case, the results were not entirely conclusive, which could be due to the large number of characteristics that can differentiate the type of physical activity practised-for example, when we refer to quantity, frequency, company of other practitioners, organisation of the same by adults, or the type of physical sport activity in terms of its objectives or competitiveness among other factors [18,22,23,26,33].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The data indicating that boys who are physically active experience less victimisation than boys who are not physically active are consistent with those of the majority of studies [9][10][11][12][13][14][15], although such relationships were not present in the sample as a whole, which is consistent with studies by different authors [16][17][18][19]. In this case, the results were not entirely conclusive, which could be due to the large number of characteristics that can differentiate the type of physical activity practised-for example, when we refer to quantity, frequency, company of other practitioners, organisation of the same by adults, or the type of physical sport activity in terms of its objectives or competitiveness among other factors [18,22,23,26,33].…”
Section: Discussionsupporting
confidence: 81%
“…However, the relationship between physical activity and the role of the perpetrator or aggressor in bullying has been less well studied. In fact, students who participate in physical activity and sports may show less aggressive attitudes and more respectful behaviour towards their peers and rules and have greater self-control [21,22]. However, when we focus specifically on bullying perpetration behaviours, the results are scarce and not very enlightening.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has demonstrated that regular sports participation may foster opportunities for social interactions and relatedness in a formal/structured context under the supervision of coaches [43,56], helping adolescents to better perceive, understand, and use their emotions to facilitate performance, as well as experiencing more feelings of self-acceptance and self-worth [10,25]. While previous research has suggested that PA and sports participation may also be associated with others' emotional appraisal and regulation of emotion [27][28][29], it was unexpected to find no significant associations or effects in the present study. Possible explanations for this finding may include the fact that interpersonal emotional regulation tends to be perceived by young athletes as less influential for performance outcomes [57] or the fact that the domain of regulation of emotion requires more complex self-regulatory processes and abilities insufficiently developed by adolescents, as shown by the lower mean scores presented in Table 1.…”
Section: Effects Of Sports Participation On Emotional Intelligence Se...mentioning
confidence: 99%
“…The study conducted by Xu and Fang (2021) establishes that one of the reasons for these behaviors in the academic environment lies in the degree of achievement in different academic tasks. Such behavior is based on the theory of self-esteem orientation, stating that when subjects cannot obtain a sufficient degree of self-esteem support, they seek other ways to improve their self-esteem ( Yiyi et al, 2022 ). When a person does not achieve the expected academic performance, a decrease in self-esteem is carried out, increasing self-esteem levels through violent behavior toward those who obtain better grades ( Xiong et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%